Analisis Faktor-Faktor Yang Menentukan Efektivitas Sistem Informasi Pada Organisasi Sektor Publik Di Wilayah Kota Surakarta - Anggraini.S, Isna (2016)
Objectives achieved in this study was to examine the effect: the support of top management, information systems management, user satisfaction, organizational culture and use of information systems on the effectiveness of information systems. This type of research is descriptive quantitative research by questionnaire directly to the respondents, the employee or the employee user information system in PT. PLN. and Pos Indonesia Surakarta as many as 34 people and processed using SPSS version 16 o'clock. The analytical tool used by multiple regression analysis, t test, and test F. The results showed that: 1) the support of top management does not affect the effectiveness of information systems; 2) management information system does not affect the effectiveness of information systems; 3) User satisfaction influence the effectiveness of information systems; 3) Cultural organizations do not affect the effectiveness of information systems; 4) The use of information systems influence the effectiveness of information systems in public sector organizations in the city of Surakarta. It was concluded that there is significant influence between user satisfaction and system usage information on the effectiveness of information systems and there is no significant influence of top management support, management information systems and organizational culture on the effectiveness of public sector information systems in the city of Surakarta.